The Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Isra Mira NIta; Gusganda Suria Manda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Financial performance is the basis of an assessment to measure whether or not the company's performance is good. Financial performance can be seen in the financial statements in the form of financial ratios, where in this study to measure the financial performance of state-owned companies using Return Of Asset (ROA). The purpose of this research is to find out, analyze and explain Good Corporate Governance (GCG), company size on financial performance at Badan Usaha Milik Negara (BUMN) listed on the Indonesia Stock Exchange in 2015-2018. This type of research is descriptive quantitative with secondary data sources, the sample selection in this study using purposive sampling method and the method of testing this research using multiple linear regression analysis method. The number of samples in this study were 17 state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2015-2018. Based on the results of the study, it can be concluded that Good Corporate Governance (GCG) and company size on financial performance in Badan Usaha Milik Negara (BUMN) is 0.203 which means 20.30% Good Corporate Governance (GCG), company size affects financial performance, while the remaining 79.70% is influenced by other factors. And based on the results of the hypothesis obtained, there is a significant positive influence between the Board of Commissioners, the Audit Committee, the Board of Directors and Company Size on the financial performance of BUMN companies for the 2015-2018 period. Keywords: Good Corporate Governance, Company Size, Return Of Asset.